2017
DOI: 10.1186/s40580-017-0110-5
|View full text |Cite|
|
Sign up to set email alerts
|

Understanding dual precipitation strengthening in ultra-high strength low carbon steel containing nano-sized copper precipitates and carbides

Abstract: Low carbon ferritic steel alloyed with Ti, Mo and Cu was hot rolled and interrupt cooled to produce nano-sized precipitates of copper and (Ti,Mo)C carbides. The steel had a tensile strength of 840 MPa, an increase in yield strength of 380 MPa over that of the plain carbon steel and reasonable ductility. Transmission electron microscopy and small angle neutron scattering were used to characterize size and volume fraction of the precipitates in the steels designed to form only copper precipitates and only (Ti,Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…It already has been observed that Ti in combination with Mo results in a considerable strength-increasing effect. The addition of 0.2 Mo and 0.09 Ti increased the yield strength and tensile strength by more than 350 MPa [17]. Further, is has been shown that the precipitation kinetics of Ti precipitates are favored, especially in the temperature range around 1000 -900 °C [18].…”
Section: Discussionmentioning
confidence: 96%
“…It already has been observed that Ti in combination with Mo results in a considerable strength-increasing effect. The addition of 0.2 Mo and 0.09 Ti increased the yield strength and tensile strength by more than 350 MPa [17]. Further, is has been shown that the precipitation kinetics of Ti precipitates are favored, especially in the temperature range around 1000 -900 °C [18].…”
Section: Discussionmentioning
confidence: 96%
“…2(b) shows that the phase composition of the complex phase organization is: a large amount of slate-tempered martensite + a small amount of lower bainite + a small amount of residual austenite;In order to understand the reason why the tested steel can maintain its strength basically without decreasing after tempering, Figure 2(c) further analyzed the sub-structure of martensite in the complex phase organization using TEM, and found that: a large number of martensite laths in the organization, in essence, is composed of a series of martensite lath bundles of uneven width and thickness, and in each lath bundle contains many more slender martensite laths, and the adjacent martensite laths in the same bundle Between two martensite laths basically meet the same bit direction and parallel alignment of the phase distribution characteristics, between the laths can be seen at the same time a large number of unevenly distributed high-density dislocation entanglement, the formation of dislocation cell. The analysis suggests that it is because of the existence of this martensitic phase transformation sub-structure that the tested steel has the characteristics of good mechanical properties of toughness while maintaining high strength [15][16] . Through TEM observation, it is confirmed that a small amount of lower bainite exists in the tempering structure of the tested steel, as shown in Fig.…”
Section: Effect Of Tempering Temperature On Microstructurementioning
confidence: 99%
“…After publication of the original article [ 1 ], the authors noticed one error with the following sentence in “Conclusion” section: The increment in yield strength due to precipitation strengthening in 1.65Cu steel is 158 MPa.” …”
Section: Erratum To: Nano Convergence (2017) 4:16 Doi 101186/s40580-mentioning
confidence: 99%